The Production of Corn in Sinaloa, Mexico and its Implications for the Environment - Cruz Delgado, Daniela (2019)
The substitution of crops leads to problems of contamination to the environment, mainly to soil and water. The objective of this article is to analyze the evolution of the production of white corn in Sinaloa and its implications on the environment, derived from the substitution of crops. The methodology used is the calculation of the index number of growth of the production and the area planted with corn, by crop groups and the five basic crops in Sinaloa. The period analyzed is 1980 to 2016. Sinaloa has become the main producer of white corn in recent decades; its cultivation is intensive in agrochemicals, which can cause pollution problems to soil and water. The planted area increased 287 % from 1980 to 2016, especially in irrigated areas. Cereals and vegetables are the groups that grew the most and represent 72,9 % of the value of production. The productive processes involve environmental costs such as those resulting from the application of fertilizers and pesticides, which, without adequate control, deteriorate the soil, pollute groundwater, flora, fauna and human health.